(untitled) (Bangladesh Journal of Medical Microbiology, 2016)
The study was done to detect different exotoxins among the strains of Staphylococcus aureus isolated in the department of Microbiology, Mymensingh Medical College in collaboration with the Department of Medicine under the Faculty of Veterinary Science, Bangladesh Agricultural University, Mymensingh between the periods from July, 2006 to June, 2007. A total of 40 S. aureus isolates investigated in this study were identified by standard microbiological techniques. Antimicrobial susceptibility of the isolates to Oxacillin was carried out by disk diffusion method as per recommendation of the National Committee for Clinical Laboratory Standards. Any isolate showing resistance to Oxacillin was tested again by agar dilution method to determine minimum inhibitory concentration (MIC) of Methicillin. All strains were also tested for mecA gene by Polymerase Chain Reaction (PCR) for confirmation of Methicillin resistance. Enterotoxin (A-D) and Toxic Shock Syndrome Toxin-1 (TSST-1) were detected by Reverse Passive Latex Agglutination (RPLA) test. Out of 40 S. aureus isolates, 7 (17.5%) Methicillin Resistant S. aureus (MRSA), 1 (2.5%) Methicillin Sensitive S. aureus (MSSA) produced Staphylococcal Enterotoxin A (SE-A) and 1 MRSA isolate was positive for TSST-1. In case of combined toxin production among the S. aureus isolates, 2 (5%) MSSA were found to produce SE-A and SE-B, 2 (5%) MSSA produced SE-C and SE-D, and 1 (2.5%) MRSA, 1 (2.5%) MSSA produced SE-C and TSST-1. Bangladesh J Med Microbiol 2008; 02 (02): 3-6